#TITLE_ALTERNATIVE# - LUHANSA (NIM 121 04 077), RONNY
The research was done at DOZ ramp A X/CUT 6, underground mine owned by PT. XYZ in Mimika, Papua province. The aims of this research were to observe the geological condition of the field, determine the propagation velocity of fracturing zone as well as investigate the correlation of the propagation velocity of fracturing zone as a result of production activity implementing the resistivity with dipole-dipole configuration method. The geological condition of the field was divided into 4 zones according to the data acquired. They are dry diorite, wet diorite, low intensity open fracturing diorite and high intensity open fracturing diorite. The zone was divided according to the resistivity value and data of the geological condition. The geological structure observed on the field was the result by the Ertsberg 2 fault and NE 2 fault. Due to the limitation of the measurement device, only 5 reliable data sets obtained from low intensity open fracturing zone. According to the data, the propagation velocity for that zone was 0.27 m/day before production and 2.4 m/day after production commenced. That was result of large production in the beginning of period that lead to the increase of stress at cave back. The elevation low intensity open fracturing zone was influenced by production at 97.8% and 2.2% from other factor such as dimension from drawpoint. The influence of production on HOD was 93%.